Audiovisual Ethnography, Community Cinema, and Youth Participation: Filmed and Filming Fieldwork Experiences from Chile - Víctor Villegas-Campillo (Social Sciences)
This article examines audiovisual ethnography as an anthropological method to understanding community cinema and youth participation through the audiovisual chain of a film piece, which encompasses the processes of watching, making, and exhibiting as an integrated sequence. This chain allows us to understand the dynamics of youth participation in all stages of audiovisual production, from creating an idea through production to the reception by the community. To this end, the relationship between participatory audiovisual practices and the promotion of youth mental health is explored through the case study “Aquí Nos Vemos Program”, which involves the creation of audiovisual narratives as a means of emotional and community expression. Fieldwork in Pudahuel, Santiago, Chile, provides ethnographic data on the creative audiovisual processes of young people around cinema and how these activities foster recognition and improvement of youth well-being.